Review On the Effects of Curcumin on Tumors of the Reproductive System : - Tohidian, Mostafa; Moradi, Zahra; Hekmatnia, Yasaman; Dalili, Amin; Sadeghi, Mostafa; Neshat, Seyed Sina; Jamalnia, Sheida; Reihani, Elnaz (Galen Medical Journal, 2021)
Curcumin, a polyphenolic derivative of Curcuma longa rhizome, has numerous beneficial effects, including antibacterial, anti-inflammatory, antiviral, antioxidant, antifungal, anti-ischemic, anti-cancer, hypoglycemic, nephroprotective, antirheumatic, hepato-protective, and antimutagenic. Curcumin has indicated the capability to exert anti-cancer activity by multifunctional mechanisms, such as induction of apoptosis, inhibition of cancer cell proliferation, cell cycle regulation, chemotherapeutic intestinal absorption, and modification of several cancer cell types signaling pathways. Several studies have shown that curcumin may have protective effects against tumors of the reproductive system. Reproductive system cancers may cause many undesirable physical and, especially, mental disorders. Infertility and its mental consequences, sexual problems, chemotherapy and surgery-related adverse effects, substantial economic burden, and death are the most common complications regarding the cancers of the reproductive system. By modulating several reproductive cancer hallmarks such as signaling pathways, multiple drug resistance, cancer cell growth and proliferation, tumor angiogenesis, and transcription factors, curcumin could be used as a safe, non-toxic, cheap, and easily accessible drug for treating different types of reproductive cancers. [GMJ.2021;10:e2178]